MR SPECTROSCOPY FOR VIEWING THE PHYSIOLOGY PROFILE OF THE BRAIN - Novia Putri Tsania; Dartini Dartini; Tri Asih Budiwati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Background: MR Spectroscopy is a radiological examination using MRS supporting software in the MRI modality that can show the correlation of metabolic or biochemical anatomical and physiological information contained in the body, both in normal and abnormal conditions[1]. MRS is done after a routine brain without contrast or contrast. Proton MR spectroscopy of brain tissue shows the spectral of several metabolites[2]. Some of the main metabolites in brain tissue detected by MRS are NAA, Cholin, Creatinien, and Lipid, Lactate and Myo Inositol. MRS results are in the form of a graph showing the ratio of NAA levels per cholin to the patient's body metabolites and a graph on normal metabolites forming Hunter's angle[3].Methods: This method is a qualitative research with a descriptive approach using comprehensive literatures studies.Results: MRI and MR Spectroscopy examinations in cases of brain disorders will strengthen the diagnosis by looking at changes in the pattern of metabolites in the brain. Some characteristic spectrum patterns can be used as markers of certain diseases, so they can replace biopsy. MR Spectroscopy examination showed that online game addicts had lower levels of NAA concentrations than normal people in the right frontal cortex and lower levels of choline (Cho) in the medial temporal cortex.[4].Conclusion: MR Spectroscopy does not play a role in replacing MRI imaging, but as an addition to non-invasive metabolic information that has a high degree of accuracy for diagnosing abnormalities in brain regions by evaluating spectrum patterns or metabolite ratios.